Oxford Handbook of Psychiatry, 1st Edition - Semple, David, Smyth, Roger; Burns, Jonathan; Darjee, Rajan; McIntosh, Andrew (OXFORD UNIVERSITY PRESS, 2005)
Every medical student and doctor is familiar with that strange mixture of panic and perplexity which occurs when, despite having spent what seems like endless hours studying, one is completely at a loss as to what to do when confronted with a real patient with real problems. For doctors of our generation that sense of panic was eased somewhat by the reassuring presence in the white coat pocket of the original Oxford Handbook of Clinical Medicine. A quick glance at one of its pages before approaching the patient served to refresh factual knowledge, guide initial assessment, and highlight Ã¢â‚¬Ëœnot to be missedÃ¢â‚¬â„¢ areas, allowing one to enter the room with a sense of at least initial confidence which would otherwise have been lacking. The initial months of psychiatric practice are a time of particular anxiety, when familiar medical knowledge seems of no use and the patients and their symptoms appear baffling and strange. Every new psychiatrist is familiar with the strange sense of relief when a Ã¢â‚¬ËœmedicalÃ¢â‚¬â„¢ problem arises in one of their patientsÃ¢â‚¬â„¢Ã¢â‚¬â€Ã¢â‚¬Ëœfinally something I know aboutÃ¢â‚¬â„¢. At this time, for us, the absence of a similar volume to the Oxford Handbook of Clinical Medicine for psychiatrists was keenly felt. This volume attempts to fulfil the same function for medical students and doctors beginning psychiatric training or practice. The white coat pocket will have gone, but we hope that it can provide that same portable reassurance.